Global Evidence on Profit Shifting Within Firms and Across Time - Delis, Fotis,Delēs, Manthos D.,Laeven, Luc,Ongena, Steven (SSRN, 2022)
We provide the first global estimates of profit shifting at the subsidiary-year level. Employing nonparametric estimation techniques within a mainstay model of profit shifting, we examine the subsidiary-year responses of earnings to the composite tax indicator faced by all subsidiaries of a multinational firm. Our panel includes 26,593 subsidiaries across 95 countries for the period 2009 2017. We extensively validate our results against aggregate estimates of previous studies and evidence from specific cases. We find that profit shifting decreased over this period in advanced economies but increased in other parts of the world where taxation policies are less stringent on average, consistent with tax arbitrage strategies. We also examine correlates of profit shifting, identifying that a key determinant is the subsidiaries’ ratio of intangible assets, and this channel is stronger in countries with weaker institutions. Both our new database and correlates open important avenues to analyze the sources and effects of profit shifting
10.2139/ssrn.4291888
Keywords: Arbeitspapier; Graue Literatur; Profit shifting; multinational enterprises; nonparametric estimation; intangible assets; institutional quality; global sample